2013
DOI: 10.1186/1476-069x-12-94
|View full text |Cite
|
Sign up to set email alerts
|

Modeling acute respiratory illness during the 2007 San Diego wildland fires using a coupled emissions-transport system and generalized additive modeling

Abstract: BackgroundA study of the impacts on respiratory health of the 2007 wildland fires in and around San Diego County, California is presented. This study helps to address the impact of fire emissions on human health by modeling the exposure potential of proximate populations to atmospheric particulate matter (PM) from vegetation fires. Currently, there is no standard methodology to model and forecast the potential respiratory health effects of PM plumes from wildland fires, and in part this is due to a lack of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 23 publications
(40 reference statements)
1
40
0
1
Order By: Relevance
“…Our findings are in line with Johnston et al (2002) and Thelen et al (2013) in finding increasingly significant respiratory health impacts with increasing concentrations of PM during wildfire periods.…”
Section: Discussionsupporting
confidence: 95%
“…Our findings are in line with Johnston et al (2002) and Thelen et al (2013) in finding increasingly significant respiratory health impacts with increasing concentrations of PM during wildfire periods.…”
Section: Discussionsupporting
confidence: 95%
“…For example, van der Werf et al (2010) reported that global carbon emissions from wildfires were 1.5e2.8 Pg C yr À1 during 1998e2007. As a result, global wildfires can significantly affect the ecosystems, carbon cycle, and climate as well as human health (Bowman et al, 2009;Thelen et al, 2013). On the other hand, the changing climate can significantly affect global wildfire activities by altering fire meteorology (Kloster et al, 2012;Pechony and Shindell, 2010;Marlon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 39 Although numerous studies have investigated the acute health effects of exposure to urban 40 particulate matter (PM), fewer have investigated the health impacts of exposure to wildfire PM 41 on the general population. 2 Increasing evidence suggests that wildfire PM causes adverse 42 5 A few wildfire health studies have used air pollution dispersion models 10,[23][24][25] or 66 CTMs 26, 27 to estimate air pollution levels in space and time. Interestingly, both studies that used 67 CTM output combined it with satellite aerosol optical depth (AOD) data, 26,27 but neither included 68 other variables in their analyses despite evidence that meteorological parameters can help to 69 scale vertically full-column AOD measures to ground-level PM 2.5 estimates.…”
Section: Introduction 37mentioning
confidence: 99%